Virtual graphic representation of construction equipment for developing a 3D earthwork BIM - Moon, Sungwoo; Seo, Jongwon (Journal of Civil Engineering and Management, 2017)
BIM provides a visualization of the construction design that allows a construction manager to review the construction process and the information that is associated with the progress. BIM is usually applied to modeling structural objects with parametric geometry where the sequence of process can be predefined. However, BIM technology can also be applied to objects with irregular shape where parametric modeling is not possible such as earthwork topography based on TIN (Triangular Irregular Network).The objective of this research is to develop a 3D earthwork BIM methodology and provide a graphic simulation that is capable of assisting construction equipment operators during excavation work. The 3D earthwork BIM presents a modeling technique that involves integrating hardware and software technologies. This combination of technologies is used to represent the actual excavator configuration in a 3D virtual environment. When it is applied to actual excavation work, it was proved that the 3D earthwork BIM could synchronize the virtual excavator configuration with the actual excavator configuration during excavation work in real time.